2019
DOI: 10.12973/eu-jer.8.4.1193
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Learning Anxiety on Foreign Students

Abstract: The purpose of this study is to investigate the level of anxiety in learning Chinese, discover the dominant factors of anxiety in learning Chinese language and analyze differences in Chinese language anxiety based on gender, year of study and HSK in foreign students in Wuhan, China. The research method used was quantitative using a survey approach. There are 250 foreign students as the samples, consisting of 108 male and 142 female students. The data collection technique used is questionnaire called CLAS (Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…In the current study, participants showed moderate anxiety in the context of online learning, and their anxiety had a negative correlation with and prediction for self-rated Chinese language proficiency, which is generally consistent with previous studies involving language learners of English (MacIntyre and Gardner, 1991;Horwitz, 2001;Dikmen, 2021), Japanese (Aida, 1994), Spanish (Coryell and Clark, 2009) and Chinese (Luo, 2013;Zhao et al, 2013;Luo, 2014aLuo, ,b, 2015Zhou, 2017;Basith et al, 2019;Zheng and Richard, 2021). Although some early research observed a positive influence of anxiety on L2 learning (Chastain, 1975;Kleinmann, 1977), and researchers have not reached a general consensus about the underlying mechanism for the negative impact of anxiety on SLA (Krashen, 1981(Krashen, , 1982Horwitz et al, 1986;Gardner, 1989, 1994;Gregersen, 2020), the negative impact of foreign language anxiety on L2 achievement has been widely recognized, such as reduction in cognitive performance (Gregersen, 2020), selfconfidence (Chou, 2018), willingness to communicate (Basith et al, 2019), and this negative influence could be observed at different stages (e.g., input, processing and output) of second language learning (MacIntyre and Gardner, 1994).…”
Section: Anxiety and Cfl Learningsupporting
confidence: 90%
See 3 more Smart Citations
“…In the current study, participants showed moderate anxiety in the context of online learning, and their anxiety had a negative correlation with and prediction for self-rated Chinese language proficiency, which is generally consistent with previous studies involving language learners of English (MacIntyre and Gardner, 1991;Horwitz, 2001;Dikmen, 2021), Japanese (Aida, 1994), Spanish (Coryell and Clark, 2009) and Chinese (Luo, 2013;Zhao et al, 2013;Luo, 2014aLuo, ,b, 2015Zhou, 2017;Basith et al, 2019;Zheng and Richard, 2021). Although some early research observed a positive influence of anxiety on L2 learning (Chastain, 1975;Kleinmann, 1977), and researchers have not reached a general consensus about the underlying mechanism for the negative impact of anxiety on SLA (Krashen, 1981(Krashen, , 1982Horwitz et al, 1986;Gardner, 1989, 1994;Gregersen, 2020), the negative impact of foreign language anxiety on L2 achievement has been widely recognized, such as reduction in cognitive performance (Gregersen, 2020), selfconfidence (Chou, 2018), willingness to communicate (Basith et al, 2019), and this negative influence could be observed at different stages (e.g., input, processing and output) of second language learning (MacIntyre and Gardner, 1994).…”
Section: Anxiety and Cfl Learningsupporting
confidence: 90%
“…According to most studies, anxiety was negatively associated with Chinese language achievement across a variety of contexts, although several studies did not report such a significant relationship (Zhao et al, 2013 ; Zheng and Richard, 2021 ). Learners who have been learning Chinese for longer times and have higher proficiency levels tend to experience lower levels of anxiety, which has been consistently found among CSL learners in China (Basith et al, 2019 ), CHL learners (Luo, 2015 ) and CFL learners (Luo, 2012 , 2014a , b ; Zhao et al, 2013 ; Zhou, 2017 ) in the U.S.…”
Section: Literature Reviewmentioning
confidence: 80%
See 2 more Smart Citations
“…Another aspect felt by the speakers in speaking English is anxiety which deals with a state of tension in an individual caused by uncomfortable stimulus externally (Basith et al, 2019). Regarding speaking ability, language anxiety especially speaking may be taken into account.…”
Section: Introductionmentioning
confidence: 99%